Delirium: A Survey of Healthcare Professionals' Knowledge, Beliefs, and Practices. Issue 12 (23rd November 2016) - Sinvani, Liron; Kozikowski, Andrzej; Pekmezaris, Renee; Akerman, Meredith; Wolf‐Klein, Gisele
Abstract : Objectives: To evaluate knowledge, beliefs, and practices regarding delirium of physicians, nurse practitioners (NPs), and registered nurses (RNs). Design: Anonymous cross‐sectional paper survey. Setting: New York metropolitan area tertiary care hospital. Participants: RNs, NPs, and physicians (N = 164). Measurements: The survey assessed knowledge, beliefs, and practices regarding delirium and prior delirium or geriatric training. Results: Of the 200 surveys distributed, 164 were completed (82% response rate). Of these, 61.7% were RNs, 13.6% were NPs, and 20.7% were physicians. Mean participant age was 36.3. The majority (80.1%) were female; 56.5% were white, 18.1% Asian, 8.7% Hispanic, 8.0% black, and 8.7% other. Of the seven potential barriers to delirium screening assessed, the three most frequently reported were lack of conceptual understanding of delirium (48.0%), similarity of delirium and dementia (41.4%), and the fluctuating nature of delirium (38.1%). Physicians were more likely than NPs and RNs to report being confident in identifying delirium ( P = .002) and to score higher on the delirium knowledge assessment ( P < .001). Participants who received geriatrics training were significantly more likely than those who did not to be confident in identifying delirium ( P = .005) and to score higher on overall delirium knowledge assessment ( P = .003). Conclusion: Geriatric training is associated with more confidence in delirium screening and higher delirium knowledge scores. There is an urgent need to broaden the approach to delirium education of nurses and physicians caring for hospitalized older adults using comprehensive multidisciplinary geriatric educational models.